2014
DOI: 10.1097/rct.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking History on Imaging Characteristics Among Patients With Human Papillomavirus-Positive Oropharyngeal Cancer

Abstract: Background and Purpose Human papillomavirus (HPV)-positive oropharyngeal cancers represent a distinct clinical entity with more favorable prognosis than HPV-negative oropharyngeal cancers. However, among patients with HPV-positive oropharyngeal carcinomas, those with a significant smoking history have a much worse prognosis. Recently, imaging characteristics of oropharyngeal cancers were identified as markers of poor prognosis. The purpose of this study was to determine whether nodal imaging characteristics di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This dramatic shift in the epidemiology of OPSCC is attributed both to a decline in tobacco use and an apparent increase in exposure to sexually transmitted oral HPV infection . Compared to HPV‐negative counterparts, HPV‐positive OPSCC patients are more likely to be nonsmokers, white, male, of a higher socioeconomic status, and have a history of multiple sexual partners . HPV‐positive patients also have significantly improved prognosis compared with HPV‐negative patients, with higher response rates to chemoradiation treatment, higher control rates with surgery and adjuvant treatment, and better overall survival both at diagnosis and after disease progression, relative to HPV‐negative OPSCC patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dramatic shift in the epidemiology of OPSCC is attributed both to a decline in tobacco use and an apparent increase in exposure to sexually transmitted oral HPV infection . Compared to HPV‐negative counterparts, HPV‐positive OPSCC patients are more likely to be nonsmokers, white, male, of a higher socioeconomic status, and have a history of multiple sexual partners . HPV‐positive patients also have significantly improved prognosis compared with HPV‐negative patients, with higher response rates to chemoradiation treatment, higher control rates with surgery and adjuvant treatment, and better overall survival both at diagnosis and after disease progression, relative to HPV‐negative OPSCC patients .…”
Section: Introductionmentioning
confidence: 99%
“…6,10 Compared to HPV-negative counterparts, HPV-positive OPSCC patients are more likely to be nonsmokers, white, male, of a higher socioeconomic status, and have a history of multiple sexual partners. [11][12][13][14] HPVpositive patients also have significantly improved prognosis compared with HPV-negative patients, 13,15 with higher response rates to chemoradiation treatment, 16 higher control rates with surgery and adjuvant treatment, 17 and better overall survival both at diagnosis 13,16,18 and after disease progression, relative to HPV-negative OPSCC patients. [19][20][21] Recent studies have also shown that the extent of nodal disease differs for HPV-positive and HPVnegative OPSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for HPV prediction (in the context of OPSCC) using quantitative image analysis methods, such as radiomics, have been evaluated [18,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Several previous studies [18, 47, 49-54, 56-65, 67-75] have focused on the use of radiomics signatures for prediction of HPV status, and differentiation between HPV+/-in patients with OPSCC's.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, HNC rates due to HPV have been rising, whereas the incidence of HNC associated with more traditional risk factors, such as tobacco, has decreased . The majority of HPV‐positive HNCs arise from the oropharynx, and these cancers are more common in younger patients and patients with a lower cumulative pack‐years or absent history of smoking . HPV‐positive oropharyngeal squamous cell carcinoma (OPSCC) has a better prognosis than its HPV‐negative counterpart .…”
Section: Introductionmentioning
confidence: 99%